On the Existence of the Solutions for Some Nonlinear Volterra Integral Equations. (24th June 2013) - Özdemir, İsmet; Çakan, Ümit; İlhan, Bekir
Abstract : We present a theorem which gives sufficient conditions for existence of at least one solution for some nonlinear functional integral equations in the space of continuous functions on the interval [ 0, a ] . To do this, we will use Darbo's fixed-point theorem associated with the measure of noncompactness. We give also an example satisfying the conditions of our main theorem but not satisfying the conditions described by Maleknejad et al. (2009).